2016
DOI: 10.1038/srep24430
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein (HBx)-induced abnormalities of nucleic acid metabolism revealed by 1H-NMR-based metabonomics

Abstract: Hepatitis B virus X protein (HBx) plays an important role in HBV-related hepatocarcinogenesis; however, mechanisms underlying HBx-mediated carcinogenesis remain unclear. In this study, an NMR-based metabolomics approach was applied to systematically investigate the effects of HBx on cell metabolism. EdU incorporation assay was conducted to examine the effects of HBx on DNA synthesis, an important feature of nucleic acid metabolism. The results revealed that HBx disrupted metabolism of glucose, lipids, and amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 43 publications
2
24
1
Order By: Relevance
“…3D). By contrast, the HBx and HBV co-down-regulated metabolites were related to purine and pyrimidine metabolism, which is also consistent with the documented HBx function24.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…3D). By contrast, the HBx and HBV co-down-regulated metabolites were related to purine and pyrimidine metabolism, which is also consistent with the documented HBx function24.…”
Section: Resultssupporting
confidence: 85%
“…In this study, we found that HBc promoted the expression of metabolic enzymes and the secretion of metabolites in HCC cells. Surprisingly, our results argue that HBc contributes to HBV-related metabolic dysregulation through the modulation of glycolysis and amino acid metabolism, which is significantly different from the metabolic changes in nucleic acid metabolism induced by HBx2324. Meanwhile, a recent study showed that the majority of amino acids (glycine, phenylalanine, glutamic acid, asparagine and tyrosine) were considerably up-regulated in HBV patients, compared with healthy subjects29.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…HBx expression also upregulate the transcriptional activity of the sterol regulatory element binding protein-1a (SREBP-1a) [26]. Using nuclear magnetic resonance-based metabolomics methods, it was found that HBx initially induced cellular DNA damage, then disrupted cellular nucleic acid metabolism and prevented DNA repair, inducing HCC [27]. However, there was yet a limited understanding whether HBx can remodel glucose metabolism and what functions and mechanism by which remodeling of glucose metabolism involves in promoting the stemness of HBx-expressing HCC cells.…”
Section: Introductionmentioning
confidence: 99%